دور صيانة الموارد البشرية في تحقيق الأسبقيات التنافسية للمؤسسة الإقتصادية- دراسة حالة مؤسسة حضنة حليب- - تيطراوي آمنة; بن زغدة حبيبة (جامعة الوادي University Of Eloued, 2024)
This paper aims to explore the role of human resource maintenance in achieving competitive priorities including cost, quality, delivery, flexibility, and innovation. Human resources are considered valuable and essential in all sectors, especially the production sector, where they need to be maintained to ensure the organization's effectiveness. The study consisted of a sample of 60 individuals from the top, middle, and lower levels of management in the active "Hodna" lait company in the industrial zone of M'sila, Algeria. A questionnaire was used to collect data, and statistical software (SPSS) was used to analyze the data. The study found that the success or failure of the company is closely related to the level of performance efficiency of maintenance workers. Therefore, the "Hodna Lait" company needs to rely on the three elements of integration, empowerment, and immersion in maintaining its human resources, which can raise the morale of workers, enhance their loyalty to the company, and make them more motivated and less prone to job turnover. The study recommends that Algerian production companies encourage employee freedom of expression and expand their participation to create a state of interaction and balance between different parts of the organization, cultivate trust and confidence between leaders and subordinates to support their loyalty and belonging, and train them in equipment and machinery management to achieve competitive priorities (cost reduction, high quality, speed of delivery, flexibility, and innovation).
The role of maintaining human resources in achieving the competitive priorities of the economic Enterprise A case study on Hodna Dairy Enterprise
Keywords: صيانة; المورد البشري; الصيانة البشرية; الأسبقيات التنافسية: Maintenance; Human Resource; Human Resource Maintenance; Competitive Priorities